Exploring Potential for a Personalized Medicine Approach to Smoking Cessation With an American Indian Tribe. Issue 1 (6th June 2022) - Carroll, Dana Mowls; Murphy, Sharon; Meier, Ellen; Rhodes, Kristine; Dorr, Casey; Braaten, Greg; Jacobson, Pamala A; Frizzell, Linda; Tyndale, Rachel F; Hatsukami, Dorothy; Hernandez, Carol
Abstract: Introduction: A potential precision medicine approach to smoking cessation is tailoring pharmacotherapy to a biomarker known as the nicotine metabolite ratio (NMR). Little is known about the potential impact and acceptability of this approach for American Indian (AI) persons. Aims and Methods: Tribal-academic collaboration was formed and during 2019–2020 AI adults who smoke( N = 54) were recruited to (1) examine correlations between NMR, dependence, and smoking exposure; (2) assess the extent to which pharmacotherapy preference aligned with NMR-informed recommendations; (3) explore acceptability of NMR-informed pharmacotherapy selection. Participants provided samples for assessment of salivary NMR and urinary total nicotine equivalents (TNE) and completed a questionnaire that assessed cigarettes per day (CPD), Fagerstrom Test for Cigarette Dependence (FTCD), pharmacotherapy preference, and perceptions of NMR-informed pharmacotherapy selection. Results: Significant positive correlations were observed between NMR and FTCD ( r = 0.29; p = .0383) and its abbreviated version Heaviness of Smoking Index (HIS) (r = 0.28; p =.0426). Post-hoc analyses suggest that relationships between dependence and NMR were driven by time to first cigarette. Nonsignificant, but directionally consistent, relationships were observed between NMR and CPD ( r = 0.21; p =0.1436) and TNE ( r = 0.24; p = .2906). Most participants preferred nicotine replacement therapy (71%) over varenicline (29%) and preference for pharmacotherapy matched NMR-based recommendations in 54% of participants. NMR-informed pharmacotherapy selection was supported by 62% of participants. Conclusion: In a sample of AI adults who smoke, NMR was related to cigarette dependence and about one-half of participants' pharmacotherapy preference matched their NMR-informed recommendation. There was lower acceptability of NMR-informed approach in this sample of AI adults than prior studies among white or black/African American people who smoke. Implications: Relationships between NMR, dependence, and self-preference for pharmacotherapy suggest that NMR-informed pharmacotherapy selection may have potential for enhancing smoking quitting success in this Tribe. Lower acceptability of NMR-informed pharmacotherapy in this Tribe suggests that this approach may not be equitably utilized. Future work could include identifying community-driven solutions to mitigate precision medicine concerns.